Metabolic Syndrome in Adults Receiving Clozapine; The Need for Pharmacist Support - Kathleen Hurley; Sinead O'Brien; Ciaran Halleran; Derina Byrne; Erin Foley; Jessica Cunningham; Fionnuala Hoctor; Laura J. Sahm (MDPI AG, 2023)
People who are diagnosed with treatment resistant schizophrenia (TRS) are likely to have clozapine as a therapeutic management option. There is a high prevalence of metabolic syndrome in patients receiving clozapine. To mitigate against this, monitoring of weight, waist circumference, lipid profile, glycated haemoglobin (HbA1c), fasting blood glucose (FBG) and blood pressure (BP) is recommended. The aims of this study were to examine the prevalence of metabolic syndrome and whether any variables were correlated with its development, and to highlight any opportunities for the pharmacist to offer support. This study was conducted in an urban hospital and its associated Clozapine Clinic in Cork, Ireland. A retrospective audit assessed the prevalence of metabolic syndrome using the International Diabetes Federation (IDF) criteria. Patients were eligible for inclusion if they were aged 18 years or more, registered with the Clozapine Clinic, and had the capacity to provide informed consent. All data were entered into Microsoft® Excel ® (Microsoft Corporation) and further statistical analysis was undertaken using R, t-tests, Fisher's Exact Test and Mann-Whitney U tests as appropriate, and p ≤ 0.05 was considered statistically significant. Of 145 patients (32% female; mean age (SD) 45.3 (±11.7) years; 86.2% living independently/in family home), nearly two thirds (n = 86, 59.3%) were diagnosed with metabolic syndrome. The mean age of participants with metabolic syndrome was 44.4 years (SD = 10.8), similar to the 46.6 years (SD = 12.8) for those without. Variables that were identified to be statistically significantly associated with metabolic syndrome included waist circumference, weight, triglycerides, high density lipoprotein-cholesterol (HDL-C), BP, FBG and HbA1c. The high incidence of metabolic syndrome in this patient population highlights the need for continued physical health monitoring of these patients to ameliorate the risk of developing metabolic syndrome.